The use of geographic information systems (GIS) and remote sensing on the matchless amphibolite belt (MAB), gorob-hope area, Namibia - Kaasheka, Elina K (My University, 2018)
The Matchless Amphibolite Belt (MAB) is a linear geological feature up to 3 kilometers wide and at least 350 kilometers long within the Damara Orogen of Namibia (Miller, 1983). The exact length of the belt is not well known due to the superficial cover of Kalahari sand, especially east of Windhoek, towards the border with Botswana. The Matchless amphibolite belt is associated with Neoproterozoic massive sulphide Cu-Au-(Zn-Ag) deposits (Breitkopf & Maiden, 1988; and Killick, 2000). Conventional geological and mineral exploration practices need enormous investments, a long time period plus intensive human labour especially in areas that are not easily accessible or with complex geological features such as the Gorob-Hope area. This study focused on the occurrence of mineralization in the Gorob-Hope area of the Matchless Amphibolite Belt and involved gathering, processing and interpretation of historic geological and remote sensing data using ENVI and ArcGIS software. These techniques were applied with a view to establish how the ore deposits are associated with the presence of the MAB and to establish the relationship between lithological units, the structures and the ore body localization. Application of ENVI and GIS techniques proved that it stands for an efficient and cost effective option of outlining mafic units, metasedimentary units, structures and ore body localization based on the available historical geological, and remote sensing data. The study also established that ore deposits found in the study area are controlled by structural features and are associated with MAB.
A thesis submitted to the Faculty of Science, University of Witwatersrand in partial fulfillment of the requirements for the Master of Science degree in Economic Geology October 2018
Keywords: Ecology; Remote sensing--Evaluation; Geographic information systems